Alumina powder, resin composition, and method for producing alumina powder

By mixing alumina particles with an equivalent circle diameter less than 0.3 μm and a high-speed mixer, the problems of alumina particles aggregation and coarse particles in the thermally conductive member are solved, and the combination of high thermal conductivity and film-like is achieved.

CN119604471APending Publication Date: 2025-03-11SUMITOMO CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380055576.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-04
Filing Date
2023-07-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a combination of high thermal conductivity and thin film in the thermally conductive member. Especially when alumina particles are largely bonded into the resin, problems of alumina particles agglomeration and coarse particles are prone to occur, resulting in low thermal conductivity and high difficulty in film-shaping.

Method used

Alumina powder containing alumina particles having an equivalent circle diameter less than 0.3 μm was used, and mixed with the resin through a high-speed mixer to ensure uniform dispersion and high filling rate of the alumina particles.

Benefits of technology

A thermal conductivity member with high thermal conductivity and film-like ability is realized, ensuring good dispersion and high filling of alumina powder in the resin composition, and improving thermal conductivity and film-shaping ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604471A_ABST
    Figure CN119604471A_ABST
Patent Text Reader

Abstract

This alumina powder contains alumina particles having an equivalent circle diameter of less than 0.3 [mu] m, and has a particle diameter D10 of less than 0.15 [mu] m at a cumulative 10% from the particle side of the number-based cumulative particle size distribution. The D10, the particle diameter D100 at a cumulative rate of 100% from the particle side of the number-based cumulative particle size distribution, and the particle diameter D50 at a cumulative rate of 50% from the particle side of the number-based cumulative particle size distribution satisfy formula (1): 4.0 < = (D100-D10) / D50 < = 20. The coefficient of variation CV (Na / Nb) of the particle ratio (Na / Nb) between the number of alumina particles Na having a circle-equivalent diameter of less than 0.3 [mu] m and the number of alumina particles Nb having a circle-equivalent diameter of 0.3 [mu] m or more is 0.3 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an alumina powder, a resin composition, and a method for producing the alumina powder. Background Art

[0002] Heat generated by energizing electronic components is likely to have an adverse effect on the performance of the electronic components, so it is desired to dissipate heat quickly. Therefore, the material constituting the thermally conductive member for heat dissipation is expected to have high thermal conductivity. As one of the thermally conductive members, there is a thermally conductive resin composition containing a resin and inorganic particles, and aluminum oxide particles are used as the inorganic particles.

[0003] Examples of the alumina particles include the easily sinterable alumina particles disclosed in Patent Document 1, which are alumina particles obtained by calcining aluminum hydroxide by the Bayer process and have a BET specific surface area of ​​5 to 9 m 2 / g, D10=0.1~0.2μm, D50=0.3~0.5μm, D90=0.7~2μm in particle size distribution, and 80% by mass or more of particles below 1μm, and Mg content, Na content, Si content and Ca content are specified.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-206460 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In recent years, as a thermally conductive member for heat dissipation, a sheet-like thermally conductive member with a relatively thin film thickness, for example, a thermally conductive member with a film thickness of more than ten micrometers or even several micrometers, has been required. Furthermore, the thermally conductive member is required to exhibit even higher thermal conductivity. In addition, in order to achieve high thermal conductivity, aluminum oxide particles must be uniformly dispersed in a resin at a high concentration.

[0009] However, when a large amount of alumina particles described in Patent Document 1 are added to a resin, the alumina particles tend to aggregate and coarse particles tend to form in the resin composition. As a result, it is difficult to achieve high thermal conductivity and to reduce the thickness of the thermally conductive member.

[0010] The present disclosure has been made in view of the above circumstances, and an object thereof is to provide an alumina powder having high thermal conductivity and capable of realizing a thin film thermally conductive member, a resin composition containing the alumina powder and having high thermal conductivity and capable of realizing a thin film thermally conductive member, and a method for producing the alumina powder.

[0011] Means for solving problems

[0012] Scheme 1 of the present invention is an aluminum oxide powder,

[0013] It is an aluminum oxide powder containing aluminum oxide particles having an equivalent circle diameter of less than 0.3 μm.

[0014] Among them, the particle size D10 at which 10% of the particles are accumulated from the fine particle side of the cumulative particle size distribution based on the number is less than 0.15 μm,

[0015] The above D10, the particle size D100 at which 100% of the particle size is accumulated from the microparticle side of the cumulative particle size distribution based on the number, and the particle size D50 at which 50% of the particle size is accumulated from the microparticle side of the cumulative particle size distribution based on the number satisfy the following formula (1):

[0016] When at least five viewing fields are observed at a magnification of 10,000 times, the coefficient of variation CV (Na / Nb) of the particle ratio (Na / Nb) of the number of aluminum oxide particles Na having an equivalent circle diameter of less than 0.3 μm to the number of aluminum oxide particles Nb having an equivalent circle diameter of 0.3 μm or more is 0.3 or less.

[0017] 4.0≤(D100-D10) / D50≤20 (1)

[0018] Aspect 2 of the present invention is the alumina powder according to aspect 1, wherein

[0019] The average circularity of the alumina particles having an equivalent circle diameter of less than 0.3 μm is 0.82 or more.

[0020] Aspect 3 of the present invention is the aluminum oxide powder according to aspect 1 or 2, wherein

[0021] The alumina particles having an equivalent circle diameter of less than 0.3 μm are α-alumina particles.

[0022] A fourth aspect of the present invention is a resin composition comprising the alumina powder according to any one of aspects 1 to 3 and a resin.

[0023] Aspect 5 of the present invention is the resin composition according to aspect 4, wherein

[0024] The mass ratio of the alumina powder to the resin is in the range of 85:15 to 95:5.

[0025] A sixth aspect of the present invention is a method for producing aluminum oxide powder, comprising the following steps:

[0026] a raw material preparation step of preparing a blending raw material including alumina raw material particles having an equivalent circle diameter of less than 0.3 μm and alumina raw material particles having an equivalent circle diameter of 0.3 μm or more; and

[0027] A mixing step is to mix the above-mentioned compounding raw materials using a high-speed mixer with a rotation speed of 10,000 rpm or more.

[0028] Effects of the Invention

[0029] According to the present disclosure, it is possible to provide an alumina powder having high thermal conductivity and capable of realizing a thin-film thermally conductive member, a resin composition containing the alumina powder and having high thermal conductivity and capable of realizing a thin-film thermally conductive member, and a method for producing the alumina powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM photograph of the alumina raw material particles 2 used in the examples.

[0031] Figure 2 This is a SEM photograph of the alumina raw material particles 5 used in the examples.

[0032] Figure 3 This is a diagram showing the volume-based particle size distribution of the alumina raw material particles 2 and the alumina raw material particles 5 used in the examples, measured by a laser diffraction / scattering particle size distribution measuring apparatus.

[0033] Figure 4 This is a diagram showing an example of binarization processing performed in the embodiment.

[0034] Figure 5 is a SEM image of a cross-section sample of Example 1.

[0035] Figure 6 is another SEM image of a cross-section sample of Example 1.

[0036] Figure 7 This is a SEM image of a cross-section sample of Comparative Example 1.

[0037] Figure 8 is another SEM image of the cross-section sample of Comparative Example 1.

[0038] Fig. 9 This is a SEM image of a cross-section sample of Comparative Example 3. DETAILED DESCRIPTION

[0039] The present inventors have conducted intensive studies to realize an alumina powder having high thermal conductivity and capable of realizing a thin-film thermally conductive member, a resin composition containing the alumina powder and having high thermal conductivity and capable of realizing a thin-film thermally conductive member, and further a method for producing the alumina powder. As a result, it was found that as the above-mentioned alumina powder, as long as it contains alumina particles with an equivalent circle diameter of less than 0.3μm, from the microparticle side of the cumulative particle size distribution based on the number, the cumulative 10% particle size is set as D10, the cumulative 50% particle size is set as D50, and the cumulative 100% particle size is set as D100, the range of D10 is specified, and D10, D50 and D100 satisfy the specified formula, and then when observed under specified conditions, the parameter representing the dispersion state of the alumina particles, that is, the coefficient of variation CV (Na / Nb) of the particle ratio (Na / Nb) of the number of alumina particles Na with an equivalent circle diameter of less than 0.3μm to the number of alumina particles Nb with an equivalent circle diameter of 0.3μm or more, is below a certain level.

[0040] Hereinafter, the alumina powder, the resin composition containing the alumina powder, and the method for producing the alumina powder according to the present embodiment will be described in detail in sequence.

[0041] 〔Alumina powder〕

[0042] (Contains alumina particles with an equivalent circle diameter of less than 0.3 μm)

[0043] The alumina powder of the present embodiment contains alumina particles having an equivalent circle diameter of less than 0.3 μm (hereinafter sometimes referred to as "alumina small particles"). The alumina powder of the present embodiment contains alumina small particles, and may also contain alumina particles having an equivalent circle diameter of 0.3 μm or more (hereinafter sometimes referred to as "alumina large particles") within a range that satisfies a predetermined particle size distribution described later. The lower limit of the equivalent circle diameter of the alumina small particles may be, for example, 0.01 μm. In addition, the upper limit of the equivalent circle diameter of the alumina large particles may be 3 μm or less.

[0044] (Particle size D10 at which 10% of the total particle size is accumulated from the fine particle side of the number-based cumulative particle size distribution)

[0045] The alumina powder of this embodiment has a particle size D10 (hereinafter sometimes simply recorded as "D10") of less than 0.15 μm, which is a cumulative 10% particle size from the particle side of the cumulative particle size distribution based on the number basis. By making the alumina powder contain alumina microparticles having a particle size of less than 0.15 μm as microparticles as small alumina particles, the above-mentioned alumina microparticles are present in the gaps formed between the large alumina particles, and high filling can be easily achieved, which can improve thermal conductivity. In addition, by making the above-mentioned alumina microparticles exist on the surface of relatively large alumina particles, the fluidity of the alumina powder in the resin is also improved when the resin composition is manufactured. The above-mentioned D10 is preferably less than 0.10 μm. It should be noted that from the viewpoint of the fluidity of the resin composition when it is mixed, the lower limit value of the above-mentioned D10 can be about 0.01 μm.

[0046] (Span value: (D100-D10) / D50)

[0047] The above-mentioned D10 of the alumina powder of the present embodiment, the particle size D100 at which 100% of the particle size is accumulated from the particle side of the cumulative particle size distribution based on the number, and the particle size D50 at which 50% of the particle size is accumulated from the particle side of the cumulative particle size distribution based on the number satisfy the following formula (1). Hereinafter, (D100-D10) / D50 in the following formula (1) is sometimes referred to as a "span value".

[0048] 4.0≤(D100-D10) / D50≤20 (1)

[0049] The above span value is an indicator of the width of the particle size distribution. If the above span value is less than 4.0, the difference between the particle size of the small alumina particles and the particle size of the large alumina particles becomes smaller. As a result, when the particle size of the small alumina particles is close to the particle size of the large alumina particles, it becomes difficult for the alumina particles to fill the gaps formed between the relatively large alumina particles. On the other hand, when the particle size of the large alumina particles is close to the particle size of the small alumina particles, most of the alumina powder is occupied by particles with a relatively small particle size, and as a result, it becomes difficult to ensure excellent thermal conductivity and good fluidity. The above span value is preferably 4.1 or more, more preferably 4.3 or more, and further preferably 5.3 or more.

[0050] On the other hand, if the span value exceeds 20, the particle size (D50) of the relatively large alumina particles becomes 5 μm or more. In this case, considering the particle size distribution of the large alumina particles, it becomes difficult to realize a thin film-shaped thermal conductive member, for example, a film-shaped thermal conductive member with a thickness of 10 μm or less cannot be realized. The span value is preferably 15 or less, more preferably 12 or less, further preferably 6.3 or less, and most preferably 6.0 or less.

[0051] (Coefficient of variation CV(Na / Nb) of the particle ratio (Na / Nb) of the number of alumina particles Na having an equivalent circle diameter of less than 0.3 μm to the number of alumina particles Nb having an equivalent circle diameter of 0.3 μm or more)

[0052] When the alumina powder of this embodiment is observed in at least 5 viewing fields at a magnification of 10,000 times, the coefficient of variation CV (Na / Nb) of the particle ratio (Na / Nb) of the number of alumina particles Na with an equivalent circle diameter less than 0.3 μm to the number of alumina particles Nb with an equivalent circle diameter greater than 0.3 μm satisfies 0.3 or less.

[0053] The alumina powder of this embodiment can obtain a resin composition in which the dispersibility of the alumina powder is high and the generation of agglomerated particles is suppressed, even when a large amount of alumina powder is mixed and kneaded with a resin. As a result, the thermal conductivity becomes high, and a thin film-shaped thermally conductive component can be realized. Since the alumina powder of this embodiment is different from the conventional products and shows good dispersion in the resin composition, in this embodiment, as an evaluation index of the dispersibility of the alumina powder, the coefficient of variation CV (Na / Nb) of the particle ratio (Na / Nb) of the number of alumina particles Na with an equivalent circle diameter of less than 0.3 μm and the number of alumina particles Nb with an equivalent circle diameter of more than 0.3 μm is used.

[0054] The coefficient of variation CV (Na / Nb) is obtained by observing at least five visual fields at a magnification of 10,000 times. The coefficient of variation CV (Na / Nb) may be evaluated using a scanning electron microscope.

[0055] As a method for obtaining alumina powder satisfying the above-mentioned coefficient of variation CV (Na / Nb), it is important to mix the alumina raw material particles using a high-speed mixer with a rotation speed of 10,000 rpm or more as shown in the method for producing alumina powder described later, rather than mixing the alumina raw material particles by the conventional method.

[0056] The above-mentioned coefficient of variation CV (Na / Nb) is preferably 0.25 or less, and more preferably 0.20 or less. The smaller the above-mentioned coefficient of variation CV (Na / Nb) is, the more preferable it is.

[0057] (Average roundness of alumina particles with equivalent circle diameter less than 0.3 μm)

[0058] The average circularity of the alumina particles of the alumina powder of the present embodiment whose equivalent circle diameter is less than 0.3 μm is preferably 0.82 or more. It is preferred that the circularity of the alumina small particles is high, so that the fluidity can be further improved when mixed and kneaded with the resin. The average circularity of the alumina small particles is more preferably 0.85 or more, and the higher the average circularity of the alumina small particles, the more preferred, but as long as it is 0.95 or less, the same fluidity can be ensured.

[0059] (Crystal structure of alumina particles with an equivalent circle diameter of less than 0.3 μm)

[0060] The alumina particles having an equivalent circle diameter of less than 0.3 μm in the alumina powder of the present embodiment are preferably α alumina particles. It should be noted that the so-called α alumina particles can be measured, for example, by measuring the alumina powder by powder X-ray diffraction, and comparing the peak height of the α phase (012 plane) appearing at the position of 2θ=25.6° with the peak height of other phases such as the γ phase appearing at the position of 2θ=46° from the obtained diffraction spectrum, or when evaluating using a resin composition, using a focused ion beam (FIB), using the FIB to make a thin sheet of about 0.1 μm in thickness, and confirming the particles having an equivalent circle diameter of less than 0.3 μm by electron beam diffraction.

[0061] On the other hand, the crystal structure of the alumina particles having an equivalent circle diameter of 0.3 μm or more is not limited. For example, one or more of α alumina, θ alumina, γ alumina, and δ alumina can be listed. From the viewpoint of improving thermal conductivity, the alumina particles having an equivalent circle diameter of 0.3 μm or more are also preferably α alumina particles.

[0062] [Method for producing alumina powder]

[0063] The method for producing aluminum oxide powder according to the present embodiment includes the following steps:

[0064] a raw material preparation step of preparing a blending raw material including alumina raw material particles having an equivalent circle diameter of less than 0.3 μm and alumina raw material particles having an equivalent circle diameter of 0.3 μm or more; and

[0065] A mixing step is to mix the above-mentioned compounding raw materials using a high-speed mixer with a rotation speed of 10,000 rpm or more.

[0066] (Raw material preparation process)

[0067] A mixed raw material containing alumina raw material particles having an equivalent circle diameter of less than 0.3 μm and alumina raw material particles having an equivalent circle diameter of 0.3 μm or more is prepared, but the method for producing these alumina raw material particles is not particularly limited. For example, commercial products can be used. Alternatively, the alumina raw material particles can be produced by a conventionally known method.

[0068] The average circularity of the alumina raw material particles with an equivalent circle diameter of less than 0.3 μm is preferably 0.82 or more. The average circularity of the alumina raw material particles with an equivalent circle diameter of less than 0.3 μm is more preferably 0.85 or more, and the higher the more preferred, but it may be 0.95 or less. The average circularity of the alumina raw material particles with an equivalent circle diameter of 0.3 μm or more is not particularly limited.

[0069] The alumina raw material particles having an equivalent circle diameter of less than 0.3 μm are preferably α alumina raw material particles. Examples of alumina raw material particles having an equivalent circle diameter of 0.3 μm or more include alumina raw material particles composed of one or more of α alumina, θ alumina, γ alumina, and δ alumina. From the viewpoint of obtaining an alumina powder having a high thermal conductivity, the alumina raw material particles having an equivalent circle diameter of 0.3 μm or more are also preferably α alumina raw material particles.

[0070] In order to obtain the alumina powder of this embodiment having D10 and span values ​​within the above range, the mixing ratio (mass ratio) of alumina raw particles having an equivalent circle diameter of less than 0.3 μm and alumina raw particles having an equivalent circle diameter of greater than 0.3 μm is preferably set to, for example, 40:60 to 10:90.

[0071] The above-mentioned blending raw materials may contain a silane coupling agent, a dispersant, etc. for the purpose of improving fluidity during mixing.

[0072] (Mixing process)

[0073] In order to obtain an alumina powder whose coefficient of variation CV (Na / Nb) satisfies the above range, it is important not only to prepare a raw material containing alumina raw material particles having an equivalent circle diameter of less than 0.3 μm and alumina raw material particles having an equivalent circle diameter of 0.3 μm or more, but also the mixing method of these alumina raw material particles. In the method for producing an alumina powder of the present embodiment, as a means for mixing the particles having different particle sizes, by using a high-speed mixer having a rotation speed of 10,000 rpm or more, the formation of agglomerates can be sufficiently suppressed, and an alumina powder whose coefficient of variation CV (Na / Nb) satisfies the above range can be obtained. As a result, by mixing and kneading the alumina powder with a resin, the formation of agglomerated parts of the alumina powder can be sufficiently suppressed, and a resin composition containing alumina powder with high filling and good dispersibility can be obtained.

[0074] The high-speed mixer with a rotation speed of 10000 rpm or more is a device for mixing powders at a high speed of 10000 rpm or more, and examples thereof include intermittent mills or rotor high-speed mills. With regard to the general mixing devices used in the mixing of powders in the past, such as air flow mixers, shaking mixers, Henschel mixers (all with a rotation speed of 470 to 5400 rpm), and planetary stirring mixers (with a rotation speed of 2000 rpm or less), it is difficult to break up the agglomerates of small alumina particles with an equivalent circle diameter of less than 0.3 μm, and agglomerates exist when making a resin composition. As a result, it is difficult to make a thin film-like resin composition, such as an extremely thin resin composition with a film thickness of less than 5 μm. In addition, by using a high-speed mixer, the agglomerates of small alumina particles with an equivalent circle diameter of less than 0.3 μm can be broken up and dispersed on the primary particle surface of the alumina raw material particles with an equivalent circle diameter of more than 0.3 μm. Furthermore, reagglomeration of alumina raw material particles having an equivalent circle diameter of 0.3 μm or more is prevented, and as a result, an alumina powder having a coefficient of variation CV (Na / Nb) satisfying the above range can be obtained.

[0075] [Resin composition]

[0076] The resin composition of the present embodiment includes the alumina powder of the present embodiment and a resin. By using the alumina powder of the present embodiment as, for example, a filler for a thermally conductive resin composition, a resin composition (composite material) having high thermal conductivity can be obtained.

[0077] In order to ensure the thermal conductivity of the resin composition, the proportion (mixing ratio) of the alumina powder of this embodiment contained in the resin composition is preferably 40% by volume or more, more preferably 50% by volume or more. On the other hand, from the viewpoint of ensuring the unique softness of the resin, the proportion of the above-mentioned alumina powder is preferably 90% by volume or less, more preferably 85% by volume or less. The resin composition of this embodiment is preferably highly filled with alumina powder to exert higher thermal conductivity. As a preferred embodiment of the resin composition highly filled with alumina powder, the mass ratio of the above-mentioned alumina powder to the resin can be listed as 85:15 to 95:5.

[0078] The resin used in the resin composition can be selected from thermoplastic resins, thermoplastic elastomers, and thermosetting resins. The resins may be used alone or in combination of two or more.

[0079] Examples of the thermoplastic resin include polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers, polymethylpentene, polyvinyl chloride, polyvinylidene chloride, polyvinyl acetate, ethylene-vinyl acetate copolymers, polyvinyl alcohol, polyvinyl acetal, polyvinylidene fluoride, and fluorine-based polymers such as polytetrafluoroethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polystyrene, polyacrylonitrile, styrene-acrylonitrile copolymers, acrylonitrile-butadiene-styrene copolymer (ABS) resins, polyphenylene ether copolymer (PPE) resins, modified PPE resins, aliphatic polyamides, aromatic polyamides, polyimides, polyamide-imides, polymethacrylic acid, polymethacrylates such as polymethyl methacrylate, polyacrylic acids, polycarbonates, polyphenylene sulfide, polysulfones, polyether sulfones, polyether nitrile, polyether ketones, polyketones, liquid crystal polymers, silicone resins, and ionomers.

[0080] Examples of the thermoplastic elastomer include styrene-butadiene block copolymers or hydrogenated products thereof, styrene-isoprene block copolymers or hydrogenated products thereof, styrene-based thermoplastic elastomers, olefin-based thermoplastic elastomers, vinyl chloride-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, and polyamide-based thermoplastic elastomers.

[0081] Examples of the thermosetting resin include crosslinked rubber, epoxy resin, phenolic resin, polyimide resin, unsaturated polyester resin, diallyl phthalate resin, etc. Specific examples of the crosslinked rubber include natural rubber, acrylic rubber, butadiene rubber, isoprene rubber, styrene-butadiene copolymer rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene-propylene copolymer rubber, chlorinated polyethylene rubber, chlorosulfonated polyethylene rubber, butyl rubber, halogenated butyl rubber, fluororubber, polyurethane rubber, and silicone rubber.

[0082] From the viewpoint of processability and properties, polyolefin resins, acrylic resins, polyimide resins, polyamide resins, polyamideimide resins, epoxy resins, phenolic resins, and silicone resins are preferably used.

[0083] Furthermore, in these resin compositions, as required, known additives such as a plasticizer, a curing accelerator, a coupling agent, a filler, a pigment, a flame retardant, an antioxidant, a surfactant, a compatibilizer, a weathering agent, an anti-blocking agent, an antistatic agent, a leveling agent, and a release agent may be appropriately formulated alone or in combination within a range that does not impair the effects of the invention.

[0084] The method for manufacturing the resin composition is described. By mixing the alumina powder of the present embodiment with a resin, a resin composition can be obtained. For example, when the resin is liquid (e.g., liquid epoxy resin, etc.), by mixing the liquid resin with the alumina powder and a curing agent, and curing it by heat or ultraviolet rays, a resin composition can be obtained. The curing agent, the mixing method, and the curing method can use known curing agents and methods. On the other hand, when the resin is solid (e.g., polyolefin resin, acrylic resin, etc.), by mixing the alumina powder with the resin, and mixing by known methods such as melt mixing, a target resin composition can be obtained.

[0085] The scheme of the resin composition of this embodiment includes a compound containing raw materials including aluminum oxide powder and resin, a mixture containing raw materials including aluminum oxide powder and resin, a molded product obtained by molding the mixture, and a molded body (cured product) obtained by subjecting the mixture or the molded product to, for example, a curing treatment.

[0086] As one form of the resin composition of the present embodiment, a film-like resin composition can be mentioned. As another example, a film-like resin composition having a film thickness of, for example, 10 μm or less, and further, 5 μm or less can be mentioned.

[0087] Example

[0088] The following examples are given to more specifically describe the embodiments of the present invention. The present disclosure is not limited to the following examples, and can be implemented with appropriate changes within the scope consistent with the above and the following gist, which are all included in the technical scope of the present disclosure.

[0089] [Preparation of alumina raw material particles]

[0090] As alumina raw material particles, the following alumina raw material particles 1 to 5 are prepared. It should be noted that the crystalline phase of each raw material particle is obtained by analyzing the crystal structure by X-ray diffraction. In this specification, "particle size" is a volume-based median particle size measured by a laser diffraction / scattering particle size distribution measuring device (Microtrac MT3300EXII, MicrotracBEL), which is distinguished from the above-mentioned D50.

[0091] (Alumina raw material particles 1) Trade name: AA-07 (manufactured by Sumitomo Chemical Co., Ltd.), particle size: 0.9 μm, crystal phase: α-alumina

[0092] (Alumina raw material particles 2) Developed product 1 (manufactured by Sumitomo Chemical Co., Ltd.), particle size: 0.15 μm, crystal phase: α-alumina

[0093] (Alumina raw material particles 3) Developed product 2 (manufactured by Sumitomo Chemical Co., Ltd.), particle size: 0.10 μm, crystal phase: α-alumina

[0094] (Alumina raw material particles 4) Trade name: ASFP-20 (manufactured by Denka Corporation), particle size: 0.3 μm, crystal phase: θ alumina and δ alumina

[0095] (Alumina raw material particles 5) Trade name: AKP-53 (manufactured by Sumitomo Chemical Co., Ltd.), particle size: 0.17 μm, crystal phase: α-alumina

[0096] It should be noted that the above-mentioned alumina raw material particles 2 (development product 1) are manufactured as follows. First, a seed crystal (α alumina) slurry is prepared. Specifically, after the alumina particles (raw material of the seed crystal) are dispersed in water, they are wet-crushed using a ball mill to obtain a wet-crushed product. Thereafter, the wet-crushed product is centrifuged at a rotation speed of 4000 rpm for 30 minutes to remove the precipitate to obtain a seed crystal slurry in which seed crystals are dispersed. Next, the above-mentioned seed crystal slurry and aluminum isopropoxide are mixed at a high speed and hydrolyzed to obtain an aluminum hydroxide slurry. The obtained aluminum hydroxide slurry is dried at 150°C to obtain aluminum hydroxide particles. Next, the aluminum hydroxide particles are calcined at 965°C in a gas furnace to obtain alumina raw material particles 2. In addition, for the above-mentioned alumina raw material particles 3 (development product 2), it is obtained by changing the mixing ratio of the above-mentioned aluminum isopropoxide and the seed crystal slurry in the manufacturing method of the above-mentioned alumina raw material particles 2 (development product 1).

[0097] SEM photographs of the alumina raw material particles 2 and 5 used in this example are shown in FIG. Figure 1 and Figure 2 In addition, the volume-based particle size distribution of these raw material particles measured by a laser diffraction / scattering particle size distribution measuring device (Microtrac MT3300EXII, manufactured by MicrotracBEL) is shown in Figure 3 middle.

[0098] [Preparation of alumina powder]

[0099] Alumina raw material particles 1 to 5 and a silane coupling agent (trade name: OFS-6040) were used, as shown in Table 1, and mixed in the manner of the respective mixing amounts in Examples 1 to 3 and Comparative Examples 1 to 3 to obtain a mixed raw material. Then, as shown in Table 1, the mixed raw materials were mixed in a high-speed mixer or planetary stirring to obtain an alumina powder. In the high-speed mixer mixing, a batch mill (A10 manufactured by IKA, rotation speed 20000 rpm) was used to mix for 30 seconds to obtain a mixed powder as an alumina powder. In addition, in the planetary stirring mixing, a rotation / revolution mixer (ARV-310, rotation speed 2000 rpm) was used to mix for 30 seconds to obtain a mixed powder as an alumina powder.

[0100] Using the obtained alumina powder, the particle size distribution of the alumina powder was measured as follows.

[0101] [Measurement of particle size distribution of alumina powder]

[0102] (Preparation of Resin Composition for Particle Size Distribution Measurement)

[0103] First, as a resin composition for particle size distribution measurement, the alumina powder shown in Table 1 was mixed / kneaded with an epoxy resin to obtain a molded body. The epoxy resin used was a resin obtained by mixing resin 1 (53-type epoxy main agent (manufactured by Mitsuki Co., Ltd.)) and resin 2 (53-type epoxy curing agent (manufactured by Mitsuki Co., Ltd.)) at a ratio of 2:1 (mass ratio). Each alumina powder and epoxy resin were measured in such a way that the powder filling rate became 85% by mass, mixed and kneaded using a rotation / revolution mixer (ARV-310) manufactured by THINKY Co., Ltd., and cured at room temperature for 24 hours to obtain a molded body (cured product).

[0104] (Particle size distribution measurement)

[0105] The obtained molded body was subjected to ion beam polishing using a cross-section polisher (registered trademark, SM-09010 manufactured by JEOL Ltd.) at an accelerating voltage of 6.0 kV for 12 hours to obtain a cross-section sample.

[0106] The obtained cross-section sample was fixed on a carbon tape, and a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Co., Ltd., part number: S-4800) was used to obtain a 20,000-fold SEM image at a predetermined acceleration voltage. Then, the obtained SEM image was automatically binarized using image analysis software (ImageJ) to obtain an image in which particles were extracted. An example of binarization processing is shown in Figure 4 middle. Figure 4In, it means that by Figure 4 The SEM image of A is binarized to obtain Figure 4 The binarized image shown in B. It should be noted that particles beyond the analysis range are excluded from the analysis object. For the extracted particles, a particle separation process (in the case of the above-mentioned image analysis software "ImageJ", "Watershed process") is implemented, and the equivalent circle diameter is calculated from the area of ​​each particle. Then, the particle size D10 with a cumulative 10% from the microparticle side of the cumulative particle size distribution based on the number basis, the particle size D100 with a cumulative 100% from the microparticle side of the cumulative particle size distribution based on the number basis, and the particle size D50 with a cumulative 50% from the microparticle side of the cumulative particle size distribution based on the number basis are calculated. These calculated values ​​are then used to calculate the span value of each example by the following formula (1a). The results are shown in Table 2.

[0107] Span value = (D100-D10) / D50 (1a)

[0108] [Determination of average circularity of particles with equivalent circle diameter less than 0.3 μm]

[0109] In the above-mentioned particle size distribution measurement, the area and circumference of the particles with an equivalent circle diameter less than 0.3 μm are calculated respectively. Then, the roundness of each particle with an equivalent circle diameter less than 0.3 μm is calculated by the following formula (2). From the calculated result, the average roundness of the particles with an equivalent circle diameter less than 0.3 μm is obtained. The results are shown in Table 2.

[0110] The roundness of a particle = 4 × π × area / (circumference 2 )(2)

[0111] [Determination of the coefficient of variation CV(Na / Nb) of the particle ratio (Na / Nb) of the number of particles with an equivalent circle diameter of less than 0.3 μm to the number of particles with an equivalent circle diameter of 0.3 μm or more]

[0112] The coefficient of variation CV(Na / Nb) of the particle ratio (Na / Nb) of the number of particles Na having an equivalent circle diameter of less than 0.3 μm to the number of particles Nb having an equivalent circle diameter of 0.3 μm or more is determined by the following method.

[0113] Using the above cross-sectional sample, a 10,000-fold image (magnification 10,000 times) was obtained in 5 fields of view using SEM. As in the case of the above-mentioned particle size distribution measurement, an image was obtained by automatic binarization using image analysis software (ImageJ). It should be noted that particles beyond the analysis range are excluded. For the extracted particles, a particle separation process ("Watershed process" in the case of the above-mentioned image analysis software "ImageJ") was implemented, and the equivalent circle diameter was calculated from the area of ​​each particle, and the number of particles Na below 0.3 μm and the number of particles Nb above 0.3 μm were measured. The Na / Nb of 5 fields of view was measured, and the average value, standard deviation, and coefficient of variation CV of Na / Nb were calculated. The Na / Nb of each field of view was calculated, and the average value and standard deviation of Na / Nb of multiple fields of view were calculated. Then the standard deviation of the particle ratio (Na / Nb) was divided by the average value of the particle ratio (Na / Nb) to calculate the coefficient of variation CV(Na / Nb) of the particle ratio (Na / Nb). Table 2 shows the results.

[0114] It should be noted that, in this embodiment, for the sake of convenience, the coefficient of variation CV (Na / Nb) was evaluated in a state where the obtained alumina powder was mixed with a small amount of resin, but it is considered that the evaluation result shows the same dispersion state as in a state where the above resin is not present. That is, it can be said that the above measurement results represent the dispersion state of the alumina powder.

[0115] [Presence or absence of coarse particles larger than 10 μm]

[0116] In the cross-sectional sample, images at 1,000 times magnification were acquired in five viewing fields using a SEM, and the presence or absence of coarse particles having a minor axis of 10 μm or more was confirmed using the images.

[0117] It should be noted that, as an example of the SEM image of the cross-sectional sample, the SEM image of the cross-sectional sample of Example 1 is shown in Figure 5 and Figure 6 In addition, a SEM image of a cross-sectional sample of Comparative Example 1 in which the alumina raw material particles are the same as those of Example 1 but the mixing method is different is shown in Figure 7 and Figure 8 Furthermore, the SEM image of the cross-section sample of Comparative Example 3 is shown in Fig. 9 In these photos, the black areas represent the resin. Figure 7 and Figure 8 The area surrounded by the white dashed line indicates the area where the aggregates are generated. Fig. 9 In the embodiment, only the alumina raw material particles 1 are used as the alumina powder, and the gaps between the alumina large particles are not filled. In contrast, in the SEM photograph of the alumina powder of Example 1 corresponding to the alumina powder of the present embodiment ( Figure 5 , Figure 6 ), the gaps between the large alumina particles derived from the alumina raw material particles 1 are filled with the small alumina particles derived from the alumina raw material particles 2. By achieving such a form, the heat conduction paths are increased and the thermal conductivity is improved, and it can be used as a filler with excellent heat dissipation.

[0118] [Measurement of viscosity in resin composition]

[0119] (Preparation of Resin Composition for Viscosity Measurement)

[0120] Alumina powder and resin 1 (53-type epoxy main agent, manufactured by Sankei Co., Ltd.) of each example were prepared. Then, 10 g of alumina powder and 2.5 g of resin 1 of each example were weighed, mixed and kneaded using a rotation / revolution mixer (ARV-310) manufactured by THINKY Co., Ltd., to prepare a resin composition for viscosity measurement.

[0121] (Measurement of Viscosity of Resin Composition for Viscosity Measurement)

[0122] The viscosity of the obtained viscosity-measuring resin composition was measured using a dynamic viscoelasticity measuring device ("Rheosol-G3000" manufactured by UBM). Parallel plates with a diameter of 40 mm were used at a gap of 1 mm and a shear rate of 5 s. -1 The measurement was carried out under the conditions of 25°C.

[0123] [Measurement of thermal conductivity of resin composition]

[0124] (Preparation of Resin Composition for Measurement of Thermal Conductivity)

[0125] Alumina powder of each example, resin 1 (53-type epoxy main agent, manufactured by Sankei Co., Ltd.) and resin 2 (53-type epoxy curing agent, manufactured by Sankei Co., Ltd.) as resins were prepared. Resin 1 and resin 2 were mixed in a ratio of 2:1 (mass ratio) to obtain epoxy resin. 9 g of each alumina powder and 1 g of epoxy resin were weighed into a cup, and mixed and kneaded using a rotation / revolution mixer (ARV-310) manufactured by THINKY Co., Ltd. to obtain a resin composition for thermal conductivity measurement.

[0126] (Measurement of Thermal Conductivity of Resin Composition for Thermal Conductivity Measurement)

[0127] The obtained thermal conductivity determination resin composition 2g is added to a mold with a diameter of 20mm, a pressure of 30MPa is applied to form it, and the resin is cured by leaving it at room temperature for 24 hours. Then, the cured molded body is processed into a size of 10mm square × thickness 2mm, and the surface is ground to obtain a test piece. The thermal conductivity of the thickness direction of the test piece is measured by a laser flash method using a xenon flash analyzer (NETZSCH company system, LFA467). The measurement is carried out under atmospheric atmosphere and 25°C. Moreover, the test piece with a thermal conductivity of more than 2.0 is evaluated as high thermal conductivity, and the test piece with a thermal conductivity of less than 2.0 is evaluated as low thermal conductivity. The results are shown in Table 3.

[0128] Table 1

[0129]

[0130] Table 2

[0131]

[0132] Table 3

[0133]

[0134] The following is known from the results of Tables 1 to 3. Since the shape of the aluminum oxide powder in Examples 1 to 3 is within the range specified in the present embodiment, the thermal conductivity is high, and a thin film thermal conductive component can be realized in the absence of coarse particles of 10 μm or more. In contrast, the coefficient of variation CV (Na / Nb) of Comparative Example 1 is high, and coarse particles of 10 μm or more are present, so high that the viscosity cannot be measured, and the thermal conductivity is also low. Furthermore, due to the presence of coarse particles of 10 μm or more, it becomes an example in which a thin film thermal conductive component cannot be realized. Comparative Example 2 becomes an example in which the coefficient of variation CV (Na / Nb) is high, coarse particles of 10 μm or more are present, and a thin film thermal conductive component cannot be realized. The D10 and span values ​​of Comparative Example 3 are out of the specified range, so high that the viscosity cannot be measured, and the thermal conductivity is also low.

[0135] The present application claims priority based on Japanese Patent Application No. 2022-124999, which is a Japanese patent application. Japanese Patent Application No. 2022-124999 is incorporated into the present specification by reference.

Claims

1. An aluminum oxide powder comprising aluminum oxide particles having an equivalent circle diameter of less than 0.3 μm, in, The particle size D10 at which 10% of the particles are accumulated from the fine particle side of the cumulative particle size distribution based on number is less than 0.15 μm. The D10, the particle size D100 at which 100% of the particle size is accumulated from the microparticle side of the cumulative particle size distribution based on the number, and the particle size D50 at which 50% of the particle size is accumulated from the microparticle side of the cumulative particle size distribution based on the number satisfy the following formula (1): When observing at least five viewing fields at a magnification of 10,000 times, the coefficient of variation CV (Na / Nb) of the particle ratio (Na / Nb) of the number of aluminum oxide particles Na having an equivalent circle diameter of less than 0.3 μm to the number of aluminum oxide particles Nb having an equivalent circle diameter of 0.3 μm or more is 0.3 or less, 4.0≤(D100-D10) / D50≤20 (1).

2. The aluminum oxide powder according to claim 1, wherein The average circularity of the aluminum oxide particles having an equivalent circle diameter of less than 0.3 μm is 0.82 or more.

3. The aluminum oxide powder according to claim 2, wherein The alumina particles having an equivalent circle diameter of less than 0.3 μm are α-alumina particles. 4 . A resin composition comprising the alumina powder according to claim 1 and a resin.

5. The resin composition according to claim 4, wherein The mass ratio of the aluminum oxide powder to the resin is in the range of 85:15 to 95:

5.

6. A method for producing aluminum oxide powder, comprising the following steps: a raw material preparation step of preparing a blending raw material including alumina raw material particles having an equivalent circle diameter of less than 0.3 μm and alumina raw material particles having an equivalent circle diameter of 0.3 μm or more; and A mixing step of mixing the blended raw materials using a high-speed mixer with a rotation speed of 10,000 rpm or more.

Citation Information

Patent Citations

  • Easily sinterable alumina particle

    JP2005206460A

  • Wiring board and display device

    JP2022124999A